Effectiveness of Ezetimibe in Reducing the Estimated Risk for Fatal Cardiovascular Events in Hypercholesterolaemic Patients with Inadequate Lipid Control While on Statin Monotherapy as Measured by the SCORE Model. (17th October 2010) - Sampalis, John S.; Bissonnette, Stéphane; Boukas, Stella
Abstract : Objectives . The aim of this prospective cohort, multicentre study was to assess the effect of coadministrating ezetimibe 10 mg/day with an ongoing statin on the estimated risk for Cardiovascular (CVD) mortality in patients with persistently elevated LDL-C after statin monotherapy. Methods . The Systematic Coronary Risk Evaluation (SCORE) function was used to estimate the 10-year risk for cardiovascular mortality at baseline and 6 weeks. Primary outcome measures were absolute and percent changes in estimated Coronary Heart Disease (CHD) Mortality Risk, and general CVD Mortality Risk (Total CVD Mortality Risk). Results . 825 patients were included in the analysis. Mean (SD) age was 62 (10.5) years and 62.3% were males. The mean (SD) estimated Total CVD Mortality Risk decreased from 0.068 (0.059) at baseline to 0.053 (0.046) at 6 weeks (RR = 0 .77 ; 95% CI:0.689–0.867), while the estimated CHD Mortality Risk decreased from 0.047 (0.040) at baseline to 0.034 (0.029) at 6 weeks (RR = 0 .72 ; 95% CI:0.624–0.826). Conclusions . Co-administration of ezetimibe with a statin is effective in significantly reducing the estimated risk for cardiovascular mortality as measured by the SCORE model.